An Exploration of the Link between Development, Economic Growth, and Natural Risk - Hallegatte, Stéphane (World Bank, Washington, DC, 2013)
This paper investigates the link between development, economic growth, and the economic losses from natural disasters in a normative analytical framework with an illustration on hurricane flood risks in New Orleans. It concludes that under broad conditions it is optimal for (1) the probability of disaster occurrence to decrease with income; (2) the capital at risk—and thus the economic losses in case of disaster — to increase faster than economic growth; and (3) the average annual losses to grow faster than income at low levels of development and slower than income at high levels of development. Increasing risk-taking reinforces economic growth; improving protections transfers risks from frequent low-intensity events to rare high-impact events.